2018
DOI: 10.9734/ajfar/2018/v1i1241
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metals Health Risk Index (HRI) in Human Consumption of Whole Fish and Water from Some Selected Dams in Katsina State Nigeria

Abstract: This study was conducted in the year 2016 to determine the heavy metal concentrations in whole fish (Clarias gariepinus) samples and water obtained from some selected Dams (Ajiwa, Zobe and Dannakola) in Katsina state Nigeria. The objectives were mainly to detect the presence of heavy metals in whole fish and water from some selected Dams in the study area, compare the concentration of heavy metals in samples from the selected Dams concerning the permissible limits specified by WHO/FAO and USEPA Standards. Eigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 16 publications
2
6
2
Order By: Relevance
“…From the results, the levels of the heavy metal Pb (range: 0.0851-0.4919 mg/kg) in the evaluated fish samples are higher than the maximum allowable concentration (MAC) 0.05 mg/kg. These values are higher than values reported for fish samples from some selected fresh water bodies in Katsina State" [8] and Jabi lake, Abuja [30] all in Nigeria. The range is also higher than values reported in samples from three coastal regions of Algeria [31] and the values reported for marine fish from Zhejiang, China [32].…”
Section: Resultscontrasting
confidence: 71%
See 4 more Smart Citations
“…From the results, the levels of the heavy metal Pb (range: 0.0851-0.4919 mg/kg) in the evaluated fish samples are higher than the maximum allowable concentration (MAC) 0.05 mg/kg. These values are higher than values reported for fish samples from some selected fresh water bodies in Katsina State" [8] and Jabi lake, Abuja [30] all in Nigeria. The range is also higher than values reported in samples from three coastal regions of Algeria [31] and the values reported for marine fish from Zhejiang, China [32].…”
Section: Resultscontrasting
confidence: 71%
“…"The range of Zn levels in the fish were low when compared to the Zn level reported by Mehouel et al [31] in fish samples from Algeria and higher than the values reported in a previous study in Katsina State, Nigeria [8]. But the values were within the 100 mg/kg MAC for Zn in fish" [36].…”
Section: Resultsmentioning
confidence: 74%
See 3 more Smart Citations